Influences on Academic Talent Development of Black Girls in K-12: A Systematic Review. Issue 4 (November 2021) - Davis, Brenda K.
Black girls experience numerous challenges to their academic development. This study examines the literature from the last 30 years related to the influences on the academic talent development of school-aged Black girls. Environmental and intrapersonal influences to Black girls' academic talent development are explored. Using a systematic approach, 43 articles are reviewed and summarized. Thematic analysis conducted on the results and findings sections from each article reveal four major themes related to personal attributes, racial identity, relationships, and institutions. The themes expand the understanding of the complexity of talent development of Black girls and identify several intrapersonal and environmental influences that can promote or hinder academic achievement. Implications for future research are discussed.